Trade unions in the digital age: country fiche on swedish manufacturing sector - Johansson, Jan (Luleå tekniska universitet, Arbetsvetenskap, 2021)
This country fiche has been realised within the framework of the BargainUp (Bargaining Upfront in the Digital Age) project (VS/2019/0280), co-financed by the European Commission. The project is led by the Italian metalworkers’ organization FIM-CISL, in partnership with the trade unions ACV-CSC Metea, IF Metall and UGT-FICA, respectively from Belgium, Sweden and Spain, the Workers’ Education and Training College (WETCO) of the Bulgarian trade union confederation CITUB, the Italian research centre ADAPT, the Luleå University of Technology (Sweden), the Technic University of Cartagena (Spain), the Catholic University of Leuven (Belgium) and the Office of Cooperation between the Ruhr University of Bochum and IG Metall (Germany). This country fiche has been developed thanks to a desk research, five interviews with IF Metall national trade unionists and a focus group with 18 worker representatives, organised between September and November 2020 Bargaining Upfront in the Digital Age